The energy intake, nutritional status, menarche at age, and premenstrual syndrome in female adolescents - Lestari, Chendy Tata; Kustiyah, Lilik; Khomsan, Ali (Alma Ata University Press, 2024)
Background: At present, many female adolescents experience faster growth and faster development phase, including menstruation (menarche). According to 2010 Riskesdas data, 21.3 % of female adolescents in Jambi experienced menarche at the age of ≤12 years, and disorder during menstrual cycle often experienced by female adolescents is premenstrual syndrome (PMS) with a prevalence ranging from 80-90 %. Objective: This research was conducted to analyze any differences from energy intake, nutritional status, age at menarche, and PMS incidence along with finding dominant factors of age at menarche and PMS in female adolescents in urban and rural areas of Jambi.Method: This research employed a cross sectional study design involving 200 female adolescents selected from State Junior High schools in urban and rural areas of Jambi province by a simple random sampling technique. The energy intake data collected by 2 x 24 food recall, whereas nutritional status data was collected through anthropometric measurements using Bioelectrical Impedance Analysis (BIA) and a microtoise, and age at menarche and PMS data were collected by a questionnaire. Bivariate data analysis was taken by Independent t-test, Mann-Whitney test and Spearman Rank test, while the multivariate data analysis was taken by the Logistic Regression. Results: There were significant differences found in age at menarche, energy intake, and nutritional status (HAZ and BAZ) of female adolescents in urban and rural areas (p<0.05). A significant negative relationship was found between nutritional status and age at menarche (p<0.05) and a significant positive relationship was found between nutritional status and the incidence of PMS (p<0.05). The Logistic Regression Test revealed that residence area was the dominant factor related to age at menarche (OR: 2.591 CI 95%: 1.415-4.744) and body fat percentage was the dominant factor related to the incidence of PMS (OR: 2.468 CI 95%: 1.159-5.254) .Conclusion: There are differences found in age of menarche, energy intake, and nutritional status (HAZ and BAZ) between female adolescents from urban and rural areas. There is a significant relationship between nutritional status and age at menarche to the incidence of PMS. Residential area becomes the dominant factor related to age at menarche and body fat percentage becomes the dominant factor related to the incidence of PMS. KEYWORDS: age at menarche; energy intake; female adolescents; nutritional status; PMS